Effect on Flow and Pipe Structure Behaviours From Different Pressure and Pipe Thickness for Pipeline in UTHM Biodiesel plant - Zulkifli, Faris Syahmi; Zuliazura Mohd Salleh (Progress in Engineering Application and Technology, 2022)
A pipe is a tubular section or hollow cylinder, usually of circular cross-section, used to transport substances from one location to another, through which liquids, gases, and masses of small solids can flow. One of the places are widely use piping system are in plant. It is important to know what type of pipes have in plant. This knowledge can help not only know what their life expectancy is, but also, it helps to know on how to properly take care of and maintain them. Depending on the type of pipes, thickness, and the location of the pipe. In plant, piping is a system of pipes used to convey fluids such as liquids, slurry and gases from one location to another This study involved the investigations of the velocity, pressure and stress distribution inside pipeline located at UTHM Biodiesel power plant using three different pipe wall thickness which is 2.8mm, 3.7mm and 5.1mm. The actual geometry of the pipe model were got from the actual geometric in plant. There are two variables for pressure inlet were used in this simulation which is 153KPa and 250KPa while the pressure outlet remains constant for 88KPa. The results of the analysis were used to construct risk indicator which predict the risk in pipe wall performance. All the pipe analysis performed by using Fluid-Structure Interaction (FSI) method. The risk indicator was construct with different pipe thickness in order to predict risk of the what might happen to the lifespan of the pipe. The results show that the flow and structure behavior was affected by the thickness of the pipe and the highest risk occurred at the transition of fluid from bigger diameter to the smaller section of the pipe. Pipe with 5.1mm wall thickness model records the highest outlet flowrate drop, pressure drop and maximum stress.